Perceptions of Religious Education: Is the content of Religious Education reflective of the changing religious landscape in the United Kingdom? - Boniface, Abigail (2017)
This dissertation aims to explore whether the content of Religious Education (RE) is reflective of the changing religious landscape in the United Kingdom. Pupils often question the purpose of their RE lessons and find it difficult to relate to the content, so it seems important to explore perceptions of RE today and to review how the subject has changed in a post-war society, in relation to the change in religiosity that the UK has experienced. Previous literature was reviewed to inspect the changes of RE in relation to the changes in the religious, and social, landscape of the UK. Subsequently, fifty-one teachers and forty-four pupils completed questionnaires that established their perceptions of RE. This considered the perceived aims of RE, whether teachers feel that RE meets these aims, whether pupils enjoy the subject and what content is or is not relevant. Each teacher and pupil also described the religiosity of the UK, which has allowed some deductions to be made and meaning to be constructed. This research found that the majority of pupils perceive RE to be important but not always relevant. Topics that surround life themes are more relevant compared with learning about religions and belief systems or practices. Additionally, some teachers have doubt that RE manages to meet its chief goals but have expressed the importance of the subject for pupils. Although there can be no definitive answer to the research questions here, it can be concluded that RE is usually relatable to pupils, and RE is still a very important subject in developing pupils’ ideas but the content of RE must be flexible and ever-changing to meet with the demands of an versatile and fluid society.